An Open-Label Clinical Trial of Hypothalamic Deep Brain Stimulation for Human Morbid Obesity: BLESS Study Protocol. Issue 4 (12th March 2018) - De Salles, Antonio A F; Barbosa, Daniel A N; Fernandes, Fernando; Abucham, Julio; Nazato, Debora M; Oliveira, Juliana D; Cury, Abrão; Biasi, Alexandre; Rossi, Ronaldo; Lasagno, Camila; Bueno, Priscila T; Santos, Renato H N; et al.
Abstract: BACKGROUND: Human morbid obesity is increasing worldwide in an alarming way. The hypothalamus is known to mediate its mechanisms. Deep brain stimulation (DBS) of the ventromedial hypothalamus (VMH) may be an alternative to treat patients refractory to standard medical and surgical therapies. OBJECTIVE: To assess the safety, identify possible side effects, and to optimize stimulation parameters of continuous VMH-DBS. Additionally, this study aims to determine if continuous VMH-DBS will lead to weight loss by causing changes in body composition, basal metabolism, or food intake control. METHODS: The BLESS study is a feasibility study, single-center open-label trial. Six patients (body mass index > 40) will undergo low-frequency VMH-DBS. Data concerning timing, duration, frequency, severity, causal relationships, and associated electrical stimulation patterns regarding side effects or weight changes will be recorded. EXPECTED OUTCOMES: We expect to demonstrate the safety, identify possible side effects, and to optimize electrophysiological parameters related to VMH-DBS. No clinical or behavioral adverse changes are expected. Weight loss ≥ 3% of the basal weight after 3 mo of electrical stimulation will be considered adequate. Changes in body composition and increase in basal metabolism are expected. The amount of food intake is likely to remain unchanged. DISCUSSION: The design of this study protocol is to define the safety of the procedure, the surgical parameters important for target localization, and additionally the safety of long-term stimulation of the VMH in morbidly obese patients. Novel neurosurgical approaches to treat metabolic and autonomic diseases can be developed based on the data made available by this investigation.